2008
DOI: 10.1080/02533839.2008.9671449
|View full text |Cite
|
Sign up to set email alerts
|

Two degree‐of‐freedom control for constant continuous positive airway pressure of an obstructive sleep apnea treatment system

Abstract: This paper presents a two degree-of-freedom control method for achieving constant continuous positive airway pressure (CPAP) of an obstructive sleep apnea (OSA) treatment system. After constructing a closed-loop DC brushless motor drive together with a blower and an airway module, we develop a pressure control system for achieving CPAP control. A mathematical model of the overall open-loop system is established based on the input-output data and its system parameters are sequentially determined using the recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The mathematical model describes the relation from the input signal of the motor drive to the pressure output. From actual open-loop experimental data shown in Tsai et al (2008), it is confirmed that the steady-state relation between the input voltage of the motor drive (volt) and the output pressure (unit: cmH 2 O) can be indeed modeled by curve-fitting as a quadratic equation, i.e., f (u) = r 0 + r 1 u + r 2 u 2 . Aside from the static relation, the transient behavior of the open-loop system can be experimentally approximated by the linear second-order system model, b 1 z -1 + b 2 z -2 1 + a 1 z -1 + a 2 z -2 , in terms of the z operator.…”
Section: Mathematical Modeling and Parameter Estimationmentioning
confidence: 70%
See 4 more Smart Citations
“…The mathematical model describes the relation from the input signal of the motor drive to the pressure output. From actual open-loop experimental data shown in Tsai et al (2008), it is confirmed that the steady-state relation between the input voltage of the motor drive (volt) and the output pressure (unit: cmH 2 O) can be indeed modeled by curve-fitting as a quadratic equation, i.e., f (u) = r 0 + r 1 u + r 2 u 2 . Aside from the static relation, the transient behavior of the open-loop system can be experimentally approximated by the linear second-order system model, b 1 z -1 + b 2 z -2 1 + a 1 z -1 + a 2 z -2 , in terms of the z operator.…”
Section: Mathematical Modeling and Parameter Estimationmentioning
confidence: 70%
“…In the proposed controller, the feedforward controller is designed to maintain the air pressure inside the mask at a desired setpoint under no human breathing, while the PID feedback controller is synthesized to eliminate or reduce the effect of the human breathing on the air pressure inside the mask. Notice that the transient errors must be controlled to lie within ±2 cmH 2 O according to the U.S. Food and Drug Administration (FDA) criteria for CPAP respirators (American Thoracic Society, 1994;Tsai et al, 2008). Fig.…”
Section: Overall System Descriptionmentioning
confidence: 99%
See 3 more Smart Citations